Preparation of Whey-Based Banana Beverage and its Quality Evaluation - Shrestha, Kunjal; Dahal, Abhishek (Himalayan Journal of Science and Technology, 2021)
A value-added functional beverage was formulated utilizing unprocessed whey with excellent nutritional qualities and bland flavors; along with banana juice and the required amount of sugar. Five different formulations were prepared with varying proportions of whey, banana juice, and sugar. Sensory analysis was carried out for all five formulations and based on statistical analysis the one which showed the highest value for body, color, flavor, taste, and overall acceptability was selected for further analysis (85% liquid whey and 15% banana juice). The shelf-life of the final product was observed for 30 days at room temperature (25±5°C) and refrigerated temperature (7±1ºC). A significant variation in body, color, flavor, taste, and overall acceptability were observed by varying the composition of whey and banana juice (p